Global Order in Crisis and Its Implications for Nepal - Lohani, Mohan (NCWA Annual Journal, 2026)
The global order that emerged after the Second World War was built upon multilateralism, respect for sovereignty, collective security, and rules-based economic cooperation. Institutions such as the United Nations, the World Bank, the International Monetary Fund (IMF), and later the World Trade Organization (WTO) were designed to prevent large-scale wars, stabilize economies, and promote development (UN, 1945). Despite repeated setbacks and inter-state asymmetrical relations, countries were able to maintain the order under this system to ensure peace and stability. Today, however, rupture in the global order has placed the world at a critical juncture. Geopolitical rivalries are intensifying, multilateral institutions are weakening, economic protectionism is asserting itself, democratic values are eroding, and climate change has posed a threat to the global ecosystem. For a small, landlocked, and strategically located country like Nepal, paradigm shifts in the global order have ominous implications. This article argues that understanding this evolving landscape is essential for safeguarding Nepal’s sovereignty, economic stability, and developmental aspirations